2020
DOI: 10.3390/recycling5030016
|View full text |Cite
|
Sign up to set email alerts
|

Ground Tire Rubber Recycling in Applications as Insulators in Polymeric Compounds, According to Spanish UNE Standards

Abstract: In the present research, we investigated the conceivable outcomes of using ground tire rubber (GTR) particle polymeric blends. Special methods of restoring tires that are no longer in use include GTR retreading, GTR blending destined for recycling to attain raw substances utilized in other industrial application production processes, and the valorization of GTR for power/energy generation. The recycling of end-of-life tires enables the recovery of rubber, steel, and fibers, all of which are valid on the market… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…This means that the rubber reticulated structures have difficulties admitting other material in the inner; although, with previous treatments it is possible to put fractions of waste rubber materials without metallic and textile fraction in polymeric matrices. These obtained composites can have several applications such as in playgrounds, or as elements for public works, in urban parks, and others [ 12 , 13 , 14 , 15 ]. In this case, recycling is much easier than devulcanization because it only requires the crushing and separation of the particles of GTR from whole components of tires [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This means that the rubber reticulated structures have difficulties admitting other material in the inner; although, with previous treatments it is possible to put fractions of waste rubber materials without metallic and textile fraction in polymeric matrices. These obtained composites can have several applications such as in playgrounds, or as elements for public works, in urban parks, and others [ 12 , 13 , 14 , 15 ]. In this case, recycling is much easier than devulcanization because it only requires the crushing and separation of the particles of GTR from whole components of tires [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The development of composites with a polymer matrix and crumb rubber is well described in a recent review [72]. Uses of ground tire rubber in insulation materials containing polymeric matrix are reviewed in [73]. The recycling of such composite materials leads to the production of new composites with sacrificing the product quality due to low interface quality between rubber and polymeric matrix [74].…”
Section: Applications Of Crumb Rubber As a Secondary Raw Materials Formentioning
confidence: 99%
“…Recent research works explore waste composite polymeric materials as potential materials for use in electrical insulation [ 5 , 6 , 7 , 8 , 9 ], generally for low insulation requirements. The present research is shown the structural-dielectric behavior from mixtures using one of the most used polymers in the industry such as polyethylene, in its most common varieties: high density (HDPE) and low density (LDPE).…”
Section: Introductionmentioning
confidence: 99%